Kajian Potensi Dron Terhadap Penyelesaian Keselamatan dan Kesihatan Pekerjaan di Tapak Pembinaan - Azizan, Nor Nadiah Najwa; Abd Rahim, Mohd Hilmi Izwan (Research in Management of Technology and Business, 2023)
The construction industry is the most important industry in the development of the country. The speed of the economy in increasing development in the country has an impact on the safety and health aspects of construction sites. Therefore, the use of drone technology helps in reducing accidents at construction sites. Drone technology is a tool used on construction sites for the purpose of monitoring works on construction sites. However, the use of drone technology in the construction industry is still at a low level. Two objectives have been designed which is to identify the current use of drones in the management of occupational safety and health at construction sites and to identify the potential of drones in aspects of occupational safety and health at construction sites. The scope of this study focuses on G7 grade contractors located around the state of Selangor. 341 contractors were selected from the total population of 3028 selected to be respondents for this study and only 105 respondents responded to the questionnaire. This study uses a quantitative method through a questionnaire. Next, the Statistical Science Social Package (SPSS) software was used to analyze the data. Descriptive statistical analysis including frequency distribution and mean score is required to identify the current and potential use of drones in aspects of occupational safety and health on construction sites. The results of the study show that the use and potential of drones can be applied to occupational health and safety solutions at construction sites.